Themes and theories : selected essays, speeches, and writings in international law / volume 2 - Higgins, Rosalyn (Oxford ; New York : Oxford University Press, 2009)
As President of the International Court of Justice, Rosalyn Higgins is the world's most senior judge. This two-volume set collects together all of her most important writings as a scholar, a member of the UN Human Rights Committee, and as a judge on the International Court of Justice.
International legal theory -- United nations law -- Use of force -- State and diplomatic immunities -- Human rights -- International petroleum law -- General -- Tributes to colleagues -- The judicial years -- The years as president of the international court of justice.
Includes bibliographical references and index.
SOL
Karim International
Keywords: International law; Law